Microbacterium telephonicum sp nov., isolated from the screen of a cellular phone - Rahi, Praveen; Kurli, Rashmi; Pansare, Aabeejjeet N.; Khairnar, Mitesh; Jagtap, Shubhangi; Patel, Nisha B.; Dastager, Syed G.; Lawson, Paul A.; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2018)
A cultivation-based study of the microbial diversity of cellular phone screens led to the isolation of a Gram-stain-positive, aerobic, rod-shaped and non-endospore-forming bacterium, designated S2T63(T), exhibiting phenotypic and genotypic characteristics unique to the type strains of closely related species. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the strain is a member of Microbacterium, and most closely related to Microbacterium aurantiacum IFO 15234(T) and Microbacterium kitamiense Kitami C2(T). The DNA-DNA relatedness values of the strain S2T63(T) to M. aurantiacum KACC 20510(T), M. kitamiense KACC 20514(T) and Microbacterium laevaniformans KACC 14463(T) were 65% (+/- 4), 29.5% (+/- 3) and 55.9% (+/- 4), respectively. The genomic DNA G+C content was 71.8 mol%. The major fatty acids were anteiso C-15:0, iso-C-16 : 0, C-16 : 0 and anteiso-C-17 : 0. The main polar lipids were diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and two unidentified polar lipids. The peptidoglycan contained the amino acids glycine, lysine, alanine and glutamic acid, with substantial amounts of hydroxy glutamic acid detected, which is characteristic of peptidoglycan type B1 alpha. The predominant menaquinones were MK-12 and MK-13. Rhamnose, fucose and galactose were the whole-cell sugars detected. The strain also showed biofilm production, estimated by using crystal violet assay. Based on the results of the phenotypic and genotypic characterizations, it was concluded that the new strain represents a novel species of the genus Microbacterium, for which the name Microbacterium telephonicum is proposed, with S2T63(T) (=MCC 2967 T = KACC 18715 T = LMG 29293(T)) as the type strain.
Keywords: actinobacteria; bio-film; MALDI-TOF MS; mobile phone